Doping - Pérez Triviño, José Luis (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
This paper aims to provide an overview of two aspects of doping. Firstly, I provide a short chronicle of the evolution of doping and on the other hand an overview of the fight against doping up to the present time where organizations like the AMA have developed a relentless struggle against it. In the second part of the work I focus the attention into the main arguments that such persecution is based. Finally I point out some criticisms of such arguments, so I question the current intensity and extent of the fight against doping.
Keywords: doping; evolution of doping; fight against doping; sport; paternalism